The subjective financial well-being of emerging adults in Malaysia: the role of expectation and value - Ngui, Jia Xian; Tan, Wei Jian; Tan, Zhe Ye; Tee, Qing Wei; Wong, Yong Jie (2022)
Subjective financial well-being plays an important role in maintaining the overall well-being of individuals. It is found that subjective financial well-being is linked to the personal and mental health of an individual. Individuals with high subjective financial well-being tend to have less personal and mental health problems. The aim of this research is to determine the impact of expectation and value on the subjective financial well-being of emerging adults. To determine the impact of expectation and value on the subjective financial well-being, this research has used the primary data of 385 respondents. After obtaining a sufficient amount of data, the data transformed into information with the use of SPSS and to form a model among the variables. The findings of this research shows that the goal expectation, materialism, and income security have a positive relationship with the subjective financial well-being whereas the financial anxiety has a negative relationship with the subjective financial well-being. The results imply that the expectation and values of an individual plays an important role in determining the subjective financial well-being of emerging adults. Lastly, this study helps to provide a comprehensive framework of subjective financial well-being with variables used such as financial anxiety, income security, goal expectation, and materialism.